2002
DOI: 10.1165/ajrcmb.26.6.4743
|View full text |Cite
|
Sign up to set email alerts
|

PDE4 Inhibitors Attenuate Fibroblast Chemotaxis and Contraction of Native Collagen Gels

Abstract: Therapies that mitigate the fibrotic process may be able to slow progressive loss of function in many lung diseases. Because cyclic adenosine monophosphate is known to regulate fibroblasts, the current study was designed to evaluate the activity of selective phosphodiesterase (PDE) inhibitors on two in vitro fibroblast responses: chemotaxis and contraction of three-dimensional collagen gels. Selective PDE4 inhibitors, rolipram and cilomilast, each inhibited the chemotaxis of human fetal lung fibroblasts (HFL-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
62
1
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(68 citation statements)
references
References 28 publications
4
62
1
1
Order By: Relevance
“…We have previously demonstrated that the β2-AR-mediated decrease in keratinocyte migration is cAMP independent (Chen et al, 2002), because G proteins and cAMP appear to play an important role in the directional movement of cells towards a Journal of Cell Science 118 (9) (Arai et al, 1997;Jin et al, 2000;Kriebel et al, 2003;Meili and Firtel, 2003;Neptune and Bourne, 1997;Neptune et al, 1999;Sun and Firtel, 2003) and increasing intracellular cAMP inhibits fibroblast chemotaxis (Kohyama et al, 2001;Kohyama et al, 2002) and neutrophil chemotaxis (Armstrong, 1995), we were, therefore, interested to determine whether an increase in intracellular cAMP was responsible for the β-agonist-mediated attenuation of EF- induced directional migration. Increasing intracellular cAMP levels with an active cAMP analog (sp-cAMP), PTX or forskolin did indeed replicate the attenuation of keratinocyte galvanotaxis observed with β-adrenergic agonists, and had no effect on migration rate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have previously demonstrated that the β2-AR-mediated decrease in keratinocyte migration is cAMP independent (Chen et al, 2002), because G proteins and cAMP appear to play an important role in the directional movement of cells towards a Journal of Cell Science 118 (9) (Arai et al, 1997;Jin et al, 2000;Kriebel et al, 2003;Meili and Firtel, 2003;Neptune and Bourne, 1997;Neptune et al, 1999;Sun and Firtel, 2003) and increasing intracellular cAMP inhibits fibroblast chemotaxis (Kohyama et al, 2001;Kohyama et al, 2002) and neutrophil chemotaxis (Armstrong, 1995), we were, therefore, interested to determine whether an increase in intracellular cAMP was responsible for the β-agonist-mediated attenuation of EF- induced directional migration. Increasing intracellular cAMP levels with an active cAMP analog (sp-cAMP), PTX or forskolin did indeed replicate the attenuation of keratinocyte galvanotaxis observed with β-adrenergic agonists, and had no effect on migration rate.…”
Section: Discussionmentioning
confidence: 99%
“…They are known to regulate several aspects of chemotaxis: the chemoattractant signal is perceived by GPCRs (Merlot and Firtel, 2003), G-proteins play a role in chemotaxis (Arai et al, 1997;Jin et al, 2000;Neptune and Bourne, 1997;Neptune et al, 1999;Sun and Firtel, 2003), locally produced cAMP regulates Dictyostelium discoideum streaming during chemotaxis (Kriebel et al, 2003;Meili and Firtel, 2003), Gβ-null D. discoideum mutants show reduced galvanotaxis (Zhao et al, 2002) and increasing intracellular cAMP inhibits fibroblast chemotaxis (Kohyama et al, 2001;Kohyama et al, 2002) and neutrophil chemotaxis (Armstrong, 1995). For these reasons, we proposed to determine whether intracellular cAMP played a role in EF-mediated directional migration in keratinocytes.…”
Section: Introductionmentioning
confidence: 99%
“…[18][19][20] We also found decreased expression levels of genes encoding for members of the CXCR4 downstream signaling pathway in CML HSC including phosphoinositol-3-kinase (PI3K) 21,22 and 3-phosphoinositide-dependent protein kinase-1 (PDK1) 22 as well as atypical protein kinase C (aPKC). [22][23][24] With regard to cell migration and chemotaxis, genes encoding for hematopoietic cell-specific DOCK2, 25 PDE4, 26 and PTP4A1 27 were downregulated in CML HSC (Table 1). These results were strengthened by a BioCarta-based pathway analysis showing differential regulation of the pathways cell to cell adhesion signaling, CXCR4 signaling pathway and role of PI3K subunit p85 in actin organization and cell migration in the HSC of CML patients compared to healthy donors (Figure 3).…”
Section: The Hsc Subset Of Patients With CML Shows Impaired Migratorymentioning
confidence: 99%
“…Roflumilast antagonizing profibrotic activity of fibroblasts stimulated by tumor growth factor β (TGF-β) has been shown from in vitro study (21). Rolipram and cilomilast attenuating fibroblast chemotaxis has been shown in in experimental study (22). Roflumilast mitigates bleomycin-induced lung fibrotic remodeling in rodents (23).…”
Section: Fibroblastsmentioning
confidence: 99%
“…Cilomilast lowered pulmonary fibrosis which are pathologically quantified examination of bleomycin instilled mice (24). In vitro and animal experimental results suggest that PDE4 inhibitors may be able to inhibit fibroblast activity and, thus, have the potential to prevent of progressive fibrosis of airways and lung parenchyma (22).…”
Section: Fibroblastsmentioning
confidence: 99%